2021
DOI: 10.1038/s41598-021-82083-w
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of thymoquinone against lung intoxication induced by malathion inhalation

Abstract: Malathion is considered one of the vastest pesticides use all over the world. Malathion-inhalation toxicity commonly occurred in many occupational farmers. Therefore, this study aimed to ameliorate the possible malathion-induced pulmonary toxicity through thymoquinone administration. Forty animals were used to conduct our study, divided into five groups; G1 control group, G2 thymoquinone (50 mg/kg) group, G3 malathion group (animals inhaled 100 mg/ml/m3 for 15 min for 5 days/week for three weeks), G4 and G5 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Pesticide application in the agricultural sector has been increasing dramatically due to the rising demands of crops for food production. The continuous utilization of pesticides is encouraged by the strong perception that pesticides are highly effective in producing good quality crops, but adversely, they can be harmful to health and the environment 1 , 2 . Annually, there are 385 million cases of acute pesticide poisoning among agricultural workers reported worldwide 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticide application in the agricultural sector has been increasing dramatically due to the rising demands of crops for food production. The continuous utilization of pesticides is encouraged by the strong perception that pesticides are highly effective in producing good quality crops, but adversely, they can be harmful to health and the environment 1 , 2 . Annually, there are 385 million cases of acute pesticide poisoning among agricultural workers reported worldwide 3 .…”
Section: Introductionmentioning
confidence: 99%
“…All the gloves were tested against a highly concentrated pesticide, before the damage, with damage and after damage recovery. The SH glove was tested against malathion, a widely used chemical in pesticide formulation 1 . The finding confirms the suitability of using a self-healing polymer to fabricate a protective glove for chemical handling.…”
Section: Introductionmentioning
confidence: 99%
“…El Okle, et al [13] founded that MXtreated rabbits (250 mg/kg b.w for 90 successive days) had hepatotoxicity confirmed by attenuation of liver enzyme activities (AST, ALT, and ALP). In line Abdo, et al [70] recognized an elevation in the activity of ALP in the malathion inhaled rats. Mongi, et al [71] found statistical increases of serum ALP in rats exposed to 63 mg/kg b.w of chlorpyrifos for 2 weeks.…”
Section: Discussionmentioning
confidence: 87%
“…It just needs to be integrated into the envisaged treatment protocol -this may be applicable worldwide. While the concept of intranasal TQ delivery demands inhalation of nanoformulations [35], fortunately, even TQ delivered by the oral route reached the brain [36] and the lungs [37] in animal models, respectively. As the next step, a clinical study for proof of concept should be initiated.…”
Section: Resultsmentioning
confidence: 99%